Intimasi Digital dan Keterbukaan Diri pada Dewasa Awal: Perspektif Sosiokultural dari Pengguna Litmatch di Kota Ambon - Pattihua, Mariyam; Manuputty, Feky (Populis: Jurnal Ilmu Sosial dan Ilmu Politik, 2022)
This study examines the dynamics of self-disclosure and the formation of digital intimacy among emerging adults—young people aged 19–22—who use the Litmatch social application in Ambon, Indonesia. As a region rarely highlighted in digital sociology, Ambon presents a distinctive sociocultural landscape shaped by strong kinship values, religiosity, and social decorum. Using a qualitative approach through in-depth interviews and digital participant observation, the study reveals how Litmatch—as a semi-anonymous interaction space—enables users to explore identity and build intimacy online, free from the social expectations present in offline life. Findings indicate that practices of self-disclosure on this platform are shaped by tensions between traditional values and individual aspirations for expressive freedom. This research offers novelty by integrating the perspectives of identity sociology, media sociology, and youth studies within a culturally specific context that remains underexplored. The study concludes by emphasizing the importance of viewing digital spaces as complex arenas for identity negotiation and calls for a more contextualized and culturally sensitive development of digital sociology in Indonesia.